Microfluidic vascular models of tumor cell extravasation - Kim, Seunggyu; Wan, Zhengpeng; Jeon, Jessie S.; Kamm, Roger D. (Frontiers in Oncology, 2022)
Emerging microfluidic disease models have amply demonstrated their value in many fields of cancer research. These in vitro technologies recapitulate key aspects of metastatic cancer, including the process of tumor cell arrest and extravasation at the site of the metastatic tumor. To date, extensive efforts have been made to capture key features of the microvasculature to reconstitute the pre-metastatic niche and investigate dynamic extravasation behaviors using microfluidic systems. In this mini-review, we highlight recent microfluidic vascular models of tumor cell extravasation and explore how this approach contributes to development of in vitro disease models to enhance understanding of metastasis in vivo.